2022
DOI: 10.47836/pjst.30.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Reaction towards MHD Marginal Layer Movement of Casson Nanofluid through Porous Media above a Moving Plate with an Adaptable Thickness

Abstract: In the current workflow and heat exchange of a Casson nanoliquid across a penetrable media above a moving plate with variable thermal conductivity, adaptive thickness and chemical reaction are analyzed. First, the governing nonlinear equations of partial derivative terms with proper extreme conditions are changed into equations of ordinary derivative terms with suitable similarity conversions. Then the resulting equations are worked out using the Keller box method. The effects of various appropriate parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Ganesh and Sridhar [31] measured the solutal and thermal transport of magnetohydrodynamic Casson fluid with radiation and moving on a permeable stretchy surface. The recently published related work is cited here [18,[36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Ganesh and Sridhar [31] measured the solutal and thermal transport of magnetohydrodynamic Casson fluid with radiation and moving on a permeable stretchy surface. The recently published related work is cited here [18,[36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Later Wakif et al [37] reported in their study that the stability of the hybrid nanofuid will be significantly enhanced by decreasing the spherical size of nanoparticles. Ganesh and Sridhar [38] measured the influence of the chemically reactive Casson-type nanofluid stream above a moving plate by adaptable thickness. Then, the velocity outline declines for the magnetic, Casson, and permeability parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Many industrial processes rely on chemical reactions, including hot rolling, chemical coating of flat plates, polymer extrusion, and heat exchange [7,8]. Pure water or air cannot occur naturally since there may be distant mass in the air or water [9].…”
Section: Introductionmentioning
confidence: 99%